PENGARUH SOCIAL MEDIA MARKETING DAN ONLINE DELIVERY SERVICE TERHADAP KEPUASAN PELANGGAN PUJASERA UNGARAN KABUPATEN SEMARANG - Wenefrida Ardhian Ayu Hardiani; Rudi Prasetyo Ardi (FE Program Studi Manajemen, 2023)
This study uses a quantitative approach. In this study, the design in this research is a case study in food courts located in Ungaran City, Semarang Regency. This study aims to determine the effect of social media marketing and online delivery service on customer satisfaction. This research was conducted from March to August 2022. The research location was selected in food courts located in Ungaran City, Semarang Regency which accommodates various MSMEs, especially in the food sector. The population in this study are consumers who buy merchandise sold by traders or tenants at food courts in Ungaran City, Semarang Regency.